Pengaruh Produk Wisata, Harga dan Kualitas Pelayanan terhadap Kepuasan Pengunjung di Kampung Sanan Kota Malang - Wibiksana, Franciscus Xaverius; Estikowati, Estikowati; Alvianna, Stella (CV. Publikasi Indonesia, 2022)
Sanan Village is one of the tourist destinations in the city of Malang. Kampung Sanan is the center of tempe processed souvenirs in Malang City. Most of the population works as tempeh craftsmen, both for production and sales. This study aims to examine the effect of the variables of tourism products, prices, and service quality on visitor satisfaction in Sanan Village, Malang City. The data collection used is by distributing questionnaires conducted online, randomly with the number of respondents collected as many as 150 respondents. Data analysis in this study used multiple linear regression. Data analysis tested whether there was a significant effect of the independent variables of tourism products, prices and service quality on the dependent variable of visitor satisfaction in Sanan Village, Malang City. From the results of data processing and research tests, it was found that the variables of tourism products, and service quality had an effect on visitor satisfaction. While the price has no effect on visitor satisfaction in Kampung Sanan. If simultaneously the three independent variables, tourism products, prices, and service quality affect visitor satisfaction. The results of this study also obtained that the service quality variable had a dominant influence on visitor satisfaction in Sanan Village, Malang City. This illustrates that visitors who visit Sanan Village are satisfied with the quality of service provided by Sanan Village.